PERAN LINGKUNGAN INDUSTRI, PERILAKU KEWIRAUSAHAAN, DAN KEMAMPUAN MANAJERIAL TERHADAP KINERJA PERUSAHAAN PADA USAHA LOGAM SKALA MIKRO - Ekaputri, Shandra; Sudarwanto, Tri; Marlena, Novi (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2018)
Indonesia is one of the developing countries which has many industry players of MSMEs. One of the MSMEs is MSME of Metal in Ngingas Sidoarjo Village which is able to market products from local market, national to international market. The objectives of the research are to analyze the role of industrial environment, entrepreneurial behavior, and managerial capability applied to measure company performance. This type of descriptive research. Data collection techniques used observation, unstructured interviews, documentation, and triangulation. Research subjects are micro scale micro entrepreneurs, Village Heads, and metal organizations Ngingas Sidoarjo. The result of the research proves that the industry environment in the obstacle of new competitors, supplier strength, buyer strength, and the availability of substitute goods have a role to the company’s performance, while competitive competitor indicator does not contribute to company performance. Entrepreneurial behavior and managerial capabilities contribute to the company’s performance on micro-scale metal enterprises in Ngingas Sidoarjo